The effectiveness of manual physical therapy interventions in pediatric patients with anterior hip pain: a retrospective study. (20th October 2017) - Galleher, Mindy; Crowe, Briana; Selhorst, Mitchell
Abstract: Objectives : The purposes of this study were to: (1) assess the benefit of adding manual therapy (MT) to physical therapy care in pediatric patients with anterior hip pain; (2) assess the relative risk of adverse reactions when MT is used; and (3) report the types of MT used. Methods: This study was a retrospective chart review of patients treated in a hospital-based sports medicine clinic. The charts of 201 patients (mean age = 14.23 ± 2.15 years) met the inclusion criteria and were reviewed. Patients were grouped into those who received MT during their episode of care, and those who did not. Pain efficiency (change in pain/number of visits), number and type of adverse reactions, as well as frequency and type of manual therapy interventions used, were the outcomes of interest. Results : The mean pain efficiency was significantly less if manual therapy was performed (MT = 0.60 [95% CI 0.47–0.72], no MT = 0.80 [95% CI 0.71–0.90] p  = 0.01). There was no significant difference between groups in risk of adverse reactions (MT = 5, no MT = 5). The number of visits was significantly different between groups (MT = 9.43 ± 3.9 sessions, and no MT = 7.6 ± 5.2 sessions). Discussion : MT did not increase the risk of an adverse reaction in pediatric patients with anterior hip pain. While it appears to be a safe intervention, it did not improve pain efficiency or patient adherence. Future research should be performed to assess the effectiveness of MT, when performed by skilled therapists, in pediatric patients with hip pain in a controlled manner. Level of Evidence: 3b.